Prevalence of surgical site infection among caesarean section patients in a teaching hospital in Ekiti State, Nigeria: An eight-year review - Taiwo O. Dayo-Dada; Adeleke A. Ojo; Oluwaseyi A. Akpor (Scientific African, 2022)
Surgical site infection is one of the most common cesarean delivery complications and is a common contributor to the occurrence of puerperal sepsis and post cesarean delivery morbidities and mortalities. The main aim of this study was to determine the prevalence of surgical site infection among caesarian section patients in a teaching Hospital in Ekiti State, Nigeria. The research employed a consecutive retrospective approach. The study population was patients that had emergency and elective caesarean section in the Teaching Hospital, between January 2011 and December 2018.The sampling technique used was total enumeration. A total of 1224 (one thousand two hundred and twenty-four patients’) clinical records were used as sample size for the study. A proforma was used to extract data from patients’ records. Data collected were analyzed using descriptive statistics of table, frequency, percentages and inferential statistics of chi-square. Results of participants socio-demographic profiles showed that majority of the patients (37.4%) were between the ages 31–36 years, 56% of them were living in urban areas and 12.3% had no formal education. The findings revealed 16.01% prevalence rate of surgical site infection, which was observed more among patients aged 31–36 years (30.6%), gravida 1–2 patients (67.3%), emergency caesarian section (74.5%), patients with previous scar (43.9%) and prolonged labour (25.0%). The study also revealed a significant relationship between surgical site infection and age, type of caesarian and presence of previous scar. This study provides a clear understanding of prevalence of surgical site infection, hence the need for preventive strategies for reduction in the rate of surgical site infections among caesarian section patients. Thus, reducing its associated maternal morbidity and mortality.